Comparative efficacy of repurposed drugs lopinavir-ritonavir and darunavir-ritonavir in hospitalised COVID-19 patients: insights from a tertiary centre cohort - Dóra Paróczai; Dóra Paróczai; András Bikov; András Bikov; Andreea Blidaru; Emanuel Bobu; Ana Lascu; Ana Lascu; Cristian Ion Mot; Cristian Ion Mot; Stefan Mihaicuta; Stefan Mihaicuta; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundDrug repurposing has become a widely adopted strategy to minimise research time, costs, and associated risks. Combinations of protease inhibitors such as lopinavir and darunavir with ritonavir have been repurposed as treatments for COVID-19. Although lopinavir-ritonavir (LPV/r) and darunavir-ritonavir (DRV/r) have shown in vitro efficacy against COVID-19, the results in human studies have been inconsistent. Therefore, our objective was to compare the efficacy of LPV/r and DRV/r in COVID-19 patients admitted to a tertiary centre in Romania.Research design and methodsA clinical dataset from 417 hospitalised patients was analysed. Patients were assigned to the LPV/r, DRV/r, or control (standard-of-care) group based on clinical decisions made by the attending infectious disease specialists, aligned with national treatment protocols. Kaplan-Meier and Cox proportional hazards regression analyses were conducted to compare in-hospital mortality and to identify factors associated with clinical improvement or fatal outcomes.ResultsBy day 10, more patients showed improvement with LPV/r and DRV/r (p=0.03 and 0.01, respectively), but only LPV/r was associated with improved survival compared to the control group (p=0.05). Factors associated with mortality included male gender (HR: 3.63, p=0.02), diabetes (HR: 2.49, p=0.03), oxygen saturation below 90% at admission (HR: 5.23, p<0.01), high blood glucose levels (HR: 3.68, p=0.01), age (HR: 1.04, p=0.02), and more than 25% lesion extension on chest CT scan (HR: 2.28, p=0.03).ConclusionsLPV/r, but not DRV/r, showed a survival benefit in patients hospitalised with COVID-19, but these findings deserve further investigation in a randomised clinical trial.